Sperm DNA damage compromises embryo development, but not oocyte fertilisation in pigs - Yentel Mateo-Otero; Marc Llavanera; Sandra Recuero; Ariadna Delgado-Bermúdez; Isabel Barranco; Jordi Ribas-Maynou; Marc Yeste (Biological Research, 2022)
Abstract Background The assessment of sperm DNA integrity has been proposed as a complementary test to conventional mammalian semen analysis. In this sense, single-strand (SSB) and double-strand (DSB) DNA breaks, the two types of sperm DNA fragmentation (SDF), have been reported to have different aetiologies and to be associated to different fertility outcomes in bovine and humans. Considering that no studies in porcine have addressed how SDF may affect sperm quality and fertility outcomes, the present work aimed to determine the impact of global DNA damage, SSB and DSB on sperm quality and in vitro fertilising ability. To this end, 24 ejaculates (one per boar) were split into three aliquots: the first was used to assess sperm quality parameters through a computer-assisted sperm analysis (CASA) system and flow cytometry; the second was used to perform in vitro fertilisation, and the third, to evaluate sperm DNA integrity using alkaline and neutral Comet assays. Results The results showed that global DNA damage negatively correlates (P < 0.05) with normal sperm morphology (R = − 0.460) and progressive motility (R = − 0.419), and positively with the percentage of non-viable sperm (R = 0.507). Multiple regression analyses showed that non-viable sperm were related to SSB (β = − 0.754). In addition, while fertilisation did not seem to be affected by sperm DNA integrity, global DNA damage, DSB and SSB were found to be correlated to embryo development outcomes. Specifically, whereas global DNA damage and DSB negatively affected (P < 0.05) the later preimplantation embryo stages (percentage of early blastocyst/blastocyst D6: for global DNA damage, R = − 0.458, and for DSB, R = − 0.551; and percentage of hatching/hatched blastocyst D6: for global DNA damage, R = − 0.505, and for DSB, R = − 0.447), global DNA damage and SSB had a negative impact (P < 0.05) on the developmental competency of fertilised embryos (R = − 0.532 and R = − 0.515, respectively). Remarkably, multiple regression analyses supported the associations found in correlation analyses. Finally, the present work also found that the inclusion of Comet assays to the conventional sperm quality tests improves the prediction of blastocyst formation (AUC = 0.9021, P < 0.05), but not fertilisation rates (P > 0.05). Conclusion Considering all these findings, this work sets a useful model to study how SDF negatively influences fertility.